“... More Powerful than the Gods’ Vengeance”: Violence and Reconciliation in Classical Athens - Funke, Peter (Classica et Mediaevalia, 2026)
Based on Hans-Joachim Gehrke’s foundational research on the anchoring of revenge in the socio-political environment of ancient Greek societies, the omnipresence of revenge and violence as defining constituents of everyday experience is first described. The terror regime of the ‘30 Tyrants’ in Athens (404/3 BC) is then examined from the perspective of guilt, retribution and revenge. Using the term ‘organised guilt’ introduced by Hannah Arendt, specific mechanisms for securing power are identified. Finally, the significance of the amnesty that paved the way for overcoming the tyranny of the ‘30’ is determined, which at the same time also provides a key to understanding political action in the social environment of Greek societies.